Impoliteness Strategies in Online Political Discourse: A Case Study of Indonesian Netizens' Comments on Tiktok - Regita Widya Murti; Hendi Pratama; Henrikus Joko Yulianto (English Education Journal, 2024)
This study analyzes impoliteness strategies in online political discourse, specifically focusing on the comments made by Indonesian netizens on TikTok regarding the presidential and vice-presidential candidate pairs. This research employed a qualitative descriptive approach to portray the phenomenon of impoliteness in the digital realm, especially in political interactions within the context of Indonesia’s presidential election. The study applied Culpeper’s (1996) theory of impoliteness strategies, and the data were collected from the Indonesian presidential election, specifically from TikTok accounts. Comments were gathered from the Anies-Muhaimin, Prabowo-Gibran, and Ganjar-Mahfud pairs. The data used in this study consisted of 60 instances of dark humor found across three TikTok accounts of presidential and vice-presidential candidates, which were then analyzed according to five categories of impoliteness strategies: bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mock, and withhold impoliteness. The results show that dark humor is most commonly conveyed through sarcasm or mock (35%), followed by positive impoliteness (28.3%), negative impoliteness (20%), bald on record impoliteness (16.7%), and no instances of withhold impoliteness. Thus, the findings contribute to understanding how impoliteness strategies are used by netizens to express political criticism or opinions online and their impact on political discourse in Indonesia. By understanding impoliteness, we will better appreciate politeness on social media and in person.